Nocturnal Autonomic Nervous System Dynamics and Chronic Painful Temporomandibular Disorders - Nickel, J C; Gonzalez, Y M; Wu, Y; Choi, D; Liu, H; Iwasaki, L R (JDR clinical and translational research, 2025)
Chronic pain associated with temporomandibular disorders (TMDs) may reflect dynamic autonomic nervous system (ANS) effects. This pilot observational study tested the hypotheses that Characteristic Pain Intensity (CPI) scores correlated with 1) amplitude, 2) duration, and 3) power densities (amplitude/duration) of nocturnal ultradian cycling of the sympathetic and parasympathetic arms of the ANS. In accordance with institutional review board oversight and Strengthening the Reporting of Observational Studies in Epidemiology guidelines, adult subjects gave informed consent, completed Axis I and II components of Diagnostic Criteria for TMD (DC-TMD), and were trained in research protocols to record nocturnal heart rate data. Subjects were assigned to ± pain groups based on CPI scores (0 = no pain, >0 = pain). Nocturnal ultradian cycling of sympathetic and parasympathetic activities was characterized using heart rate variability measures of the percentage of the absolute value of the low-frequency power component (ms ) and normal-to-normal sinus node depolarizations >50 ms compared to total number (pNN50, %), respectively. Peaks and valleys of ultradian cycling were identified, where cycle amplitudes and durations were quantified, and sympathetic/parasympathetic power densities were calculated. The hypotheses were tested by nonparametric correlations and regression analyses, where significance was defined by < 0.05. Of 32 individuals screened and enrolled, 18 females and 11 males completed all study protocols. Subjects produced 87 nighttime electrocardiogram recordings with an average duration of 7.7 ± 1.0 h. CPI scores ranged from 0 to 70 and were significantly higher ( = 0.032) in females (30 ± 25) than in males (10 ± 17). Nocturnal ultradian sympathetic cycling in females compared to males showed significantly higher amplitudes ( = 0.011) and lower durations ( = 0.048). CPI scores were correlated with nocturnal cycling amplitude and duration (all | | ≥ 0.80) and the log of sympathetic/parasympathetic power densities ( = 0.89). Characteristic Pain Intensity scores were correlated with amplitudes, durations, and power densities of nocturnal ANS ultradian cycling.Knowledge Transfer Statement:Chronic myofascial pain may reflect autonomic nervous system (ANS) activity. Characteristic Pain Intensity scores of subjects were correlated with power densities of ANS ultradian cycling during sleep. Future research is needed to detect sex differences in ANS power densities in subjects with chronically painful temporomandibular disorders.